1990
DOI: 10.1164/ajrccm/141.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Depression during Sleep Apnea Depends on Hypoxic Chemosensitivity: A Study at High Altitude

Abstract: To clarify the heart rate (HR) slowing response during periodic breathing (PB) with apnea and its relationship to hypoxic ventilatory response (HVR), sleep studies were done in seven Japanese climbers at 5,360 m in the Kunlun mountains of China in 1986. Apnea duration (APD), arterial oxygen saturation changes (delta SaO2), and the percentage of heart rate changes (delta HR%) during PB with apnea were analyzed. The data were compared with hypoxic heart rate and ventilatory responses assessed at sea level. HR du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Phagocytes are known to play a key role in lung injury by a cascade effect: phagocytes release oxidants and proteases that damage the pulmonary endothelial and epithelial cells, thus disrupting the alveolar-capillary unit [24,25]. Glucocorticoids such as dexamethasone are used in the treatment of inflammatory lung injuries due to their ability to inhibit phagocyte migration to the site of injury and to partially suppress phagocyte reactivity [26]. Dexamethasone pretreatment has also reduced pulmonary elastase activity and chloramine levels, further supporting the anti-inflammatory effectiveness of dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytes are known to play a key role in lung injury by a cascade effect: phagocytes release oxidants and proteases that damage the pulmonary endothelial and epithelial cells, thus disrupting the alveolar-capillary unit [24,25]. Glucocorticoids such as dexamethasone are used in the treatment of inflammatory lung injuries due to their ability to inhibit phagocyte migration to the site of injury and to partially suppress phagocyte reactivity [26]. Dexamethasone pretreatment has also reduced pulmonary elastase activity and chloramine levels, further supporting the anti-inflammatory effectiveness of dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…This rise is largely the result of increased sympathetic activity triggered by stimulation of peripheral chemoreceptors contained within the carotid bodies [9]. During sleep, heart rate (HR) was found to decrease during the respiratory pause of periodic breathing cycles with SaO 2 fall [10][11][12]. These studies showed HR fluctuations during the periodic breathing cycles with the lowest values reached during apnea and the highest during hyperpnea.…”
Section: Introductionmentioning
confidence: 97%
“…This phenomenon may be related to the fact that we studied awake subjects. During sleep, a more marked in¯uence of unstable breathing control on LF¯uctuations of heart rate has been noticed (Masuyama et al 1990;Ward et al 1995). However, we observed a signi®cantly increased VLF -R intervals (normalized units) in the frequency component between 0.01 and 0.08 Hz.…”
Section: Discussionmentioning
confidence: 99%